Short-term triple therapy with azithromycin for Helicobacter pylori eradication: Low cost, high compliance, but low efficacy - Mattar Rejane; Navarro-Rodriguez Tomás; Barbuti Ricardo C; Teixeira Ana; Eisig Jaime N; Silva Fernando M (BMC Gastroenterology, 2008)
Abstract Background The Brazilian consensus recommends a short-term treatment course with clarithromycin, amoxicillin and proton-pump inhibitor for the eradication of Helicobacter pylori (H. pylori). This treatment course has good efficacy, but cannot be afforded by a large part of the population. Azithromycin, amoxicillin and omeprazole are subsidized, for several aims, by the Brazilian federal government. Therefore, a short-term treatment course that uses these drugs is a low-cost one, but its efficacy regarding the bacterium eradication is yet to be demonstrated. The study's purpose was to verify the efficacy of H. pylori eradication in infected patients who presented peptic ulcer disease, using the association of azithromycin, amoxicillin and omeprazole. Methods Sixty patients with peptic ulcer diagnosed by upper digestive endoscopy and H. pylori infection documented by rapid urease test, histological analysis and urea breath test were treated for six days with a combination of azithromycin 500 mg and omeprazole 20 mg, in a single daily dose, associated with amoxicillin 500 mg 3 times a day. The eradication control was carried out 12 weeks after the treatment by means of the same diagnostic tests. The eradication rates were calculated with 95% confidence interval. Results The eradication rate was 38% per intention to treat and 41% per protocol. Few adverse effects were observed and treatment compliance was high. Conclusion Despite its low cost and high compliance, the low eradication rate does not allow the recommendation of the triple therapy with azithromycin as an adequate treatment for H. pylori infection.